High-throughput topographic, mechanical, and biological screening of multilayer films containing mussel-inspired biopolymers - Neto, Ana I. (2016)
A high-content screening method to characterize multifunctional multilayer films that combine mechanical adhesion and favorable biological response is reported. Distinct combinations of nanostructured films are produced using layer-by-layer methodology and their morphological, physicochemical, and biological properties are analyzed in a single microarray chip. Inspired by the composition of the adhesive proteins in mussels, thin films containing dopamine-modified hyaluronic acid are studied. Flat biomimetic superhydrophobic patterned chips produced by a bench-top methodology are used for the build-up of arrays of multilayer films. The wettability contrasts imprinted onto the chips are allowed to produce individual, position controlled, multilayer films in the wettable regions. The flat configuration of the chip permits to perform a series of nondestructive measurements directly on the individual spots. In situ adhesion properties are directly measured in each spot, showing that nanostructured films richer in dopamine promote the adhesion. In vitro tests show an enhanced cell adhesion for the films with more catechol groups. The advantages presented by this platform include ability to control the uniformity and size of the multilayers films, its suitability to be used as a new low cost toolbox and for high-content cellular screening, and capability for monitoring in situ a variety of distinct material properties.